Être présente et absente simultanément : l’action furtive - Sophie Lapalu (Sillages Critiques)
Furtive actions are artworks which take place at first in the public place and which are then communicated within the field of art. In the street, these commonplace gestures realized without spectator go unnoticed for those who walk past them. In museums, what is presented is the mark of a past action. Edgar Allan Poe’s short story, The Purloined Letter, and the seminar that Jacques Lacan dedicated to it allow us to draw the structure of this type of artworks, always both present and absent simultaneously.